Future of the news function of printed press under the competition of electronic communications: a prospective study in the period 2015-2025 - Heba Ahmed Awad Goda; Ibrahim Laila Abd Elmagid (International Journal of Communication and Society, 2019)
The technological development has led to the emergence of modern means of communication, such as electronic newspapers, tablets and mobile phones. Since modern communication media has assumed growing responsibility in the reporting and dissemination of news and information, printed media has been negatively affected. This paper aims to investigate the future of the news function of printing press under the competition of electronic means in the period 2015-2025 by determining the factors affecting this function, the experts' perceptions and the possible future scenarios. By conducting interviews with experts and analyzing the contents of news items in printed and electronic newspapers, this article reveals that printed press cannot be dead because it is more effective in shaping the reader's agenda and still adheres to professional norms. Results add that online news content lacks the professional guidelines, especially the accuracy and the attribution as many of the quotes are inaccurate, or are attributed to the wrong person due to the uncontrolled freedom of posting and modifying information online.